Modern meat: the next generation of meat from cells - Anthis, JR; Berenstein, P; Beurrier, C; Biehl, C; Birdie, P; Burley, J; Chantre, C; Davis, J; Dohadwala, S; d'Origny, G; Espírito Santo, V; Espitia, F; et al. (Cellular Agriculture Society, 2023)
Modern Meat is the first textbook on cultivated meat, with contributions from over 100 experts within the cultivated meat community. The Sections of Modern Meat comprise 5 broad categories of cultivated meat: Context, Impact, Science, Society, and World. The 19 chapters of Modern Meat, spread across these 5 sections, provide detailed entries on cultivated meat. They extensively tour a range of topics including the impact of cultivated meat on humans and animals, the bioprocess of cultivated meat production, how cultivated meat may become a food option in Space and on Mars, and how cultivated meat may impact the economy, culture, and tradition of Asia.